KONSEP STABILITAS EMOSIONAL DALAM PERSPEKTIF AL-QUR’AN: ANALISIS TEMATIK TERSTRUKTUR - Euis Ramadani; Muhammad Alif (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2026)
This study aims to examine the concept of emotional stability from the perspective of the Qur’an, including its definition, factors causing instability, Qur’anic values for emotion regulation, the examples of the prophets, and its implementation in modern life. The method used is library research with a Structured Thematic Analysis (STA) approach that adopts the principles of Grounded Theory. The primary data sources are Qur’anic verses related to tranquility (ṭuma’nīnah), patience, prayer, tawakkul, and the stories of the prophets. The results show that Qur’anic emotional stability is centered on ṭuma’nīnah achieved through dhikr, patience, prayer, tawakkul, and optimism. Factors causing instability include the trait of halu’an (restlessness and complaint), lack of patience, absence of tawakkul, and despair of Allah’s mercy. Qur’anic values such as dhikr, beautiful patience (shabran jamilan), prayer as periodic emotion regulation, tawakkul, qana’ah, and ridha are proven effective in controlling emotions. The implementation of these values is relevant in workplace stress management, social media emotion regulation, and spiritually-based parenting.